All the little live things - Stegner, Wallace, 1909-1993. (New York : Viking Press, 1967)
A novel which reflects the conflicting life styles of the sixties.
Keywords: Retirees -- Fiction; Fathers and sons -- Fiction; Suicide victims -- Fiction; California -- Fiction; Psychological fiction